Phosphate rock reduces the bioavailability of heavy metals by influencing the bacterial communities during aerobic composting - Hu CUI; Yang OU; Li-xia WANG; Bai-xing YAN; Ying-xin LI; Da-wei DING (Journal of Integrative Agriculture, 2021)
Available information on the microbial mechanisms associated with heavy metal (HM) passivation during co-composting amended with phosphate rock (PR) remains limited. Thus, this study investigated the dynamic changes in bacterial communities and HM-fractions (Zn, Cu, Cd, Cr and Pb) during swine manure composting with maize straw, and ascertained the bacterial influence on HM-passivation. The results demonstrated that the addition of PR improved HM-passivation, especially for Zn and Cd, with their bioavailability factors (BFs) reduced by 247.41 and 176.25%, respectively. As for bacterial communities, the proportion of Firmicutes decreased, while the proportions of Proteobacteria, Bacteroidetes, Deinococcus-Thermus and Gemmatimonadetes increased in all treatments. PR significantly changed the primary bacterial phyla in the thermophilic phase. Bacteroidetes were the main bacterial component controlling the passivation of Zn, Cu and Cr, while Deinococcus-Thermus mainly regulated the mobility of Zn and Pb, and Proteobacteria only dominated the transformation among Cd-fractions. These results may provide a reference for the use of HM-passivation techniques during composting.